Bodies that Fester in the Holds of the “Coffin Ships”: Postcolonial Neo-Victorianism, Vulnerability and Resistance in Joseph O’Connor’s Star of the Sea (2003) - Romero Ruiz, Mª Isabel (Miscelánea: A Journal of English and American Studies, 2021)
The presence of Empire in the Victorian period and its aftermath has become a new trope in neo-Victorian studies, introducing a postcolonial approach to the re-writing of the Victorian past. This, combined with the metaphor of the sea as a symbol of British colonial and postcolonial maritime power, makes of Joseph O’Connor’s novel Star of the Sea a story of love, vulnerability and identity. Set in the winter of 1847, it tells the story of the voyage of a group of Irish refugees travelling to New York trying to escape from the Famine. The colonial history of Ireland and its long tradition of English dominance becomes the setting of the characters’ fight for survival. Parallels with today’s refugees can be established after Ireland’s transformation into an immigration country. Following Judith Butler’s and Sarah Bracke’s notions of vulnerability and resistance together with ideas about ‘the other’ in postcolonial neo-Victorianism, this article aims to analyse the role of Empire in the construction of an Irish identity associated with poverty and disease, together with its re-emergence and reconstruction through healing in a contemporary globalised scenario. For this purpose, I resort to Edward Said’s and Michael Hardt and Antonio Negri’s ideas about imperialism and new imperialism along with Elizabeth Ho’s concept of ‘the Neo-Victorian-at-sea’ and some critics’ approaches to postcolonial Gothic. My main contention throughout the text will be that vulnerability in resistance can foster healing.